Predicting antenna pattern degradations in microstrip reflectarrays through interval arithmetic. Issue 8 (1st June 2016) - Rocca, Paolo; Poli, Lorenzo; Anselmi, Nicola; Salucci, Marco; Massa, Andrea
Abstract : The effects on the antenna power pattern of the tolerances in etching the microstrip patches and in the knowledge of the substrate characteristics of reflectarray antennas are predicted with an approach based on the arithmetic of intervals and the interval analysis ( IA ). The uncertainties on the geometric and electric antenna parameters are defined as intervals and the rules of IA are applied to determine the bounds of deviation of the actual power pattern with respect to the nominal pattern. A set of representative results is reported to validate the proposed approach and to show its reliability and efficiency when considering different tolerance errors and various operational conditions.